2016
DOI: 10.1177/2325957416636475
|View full text |Cite
|
Sign up to set email alerts
|

Physician Preferences for Physician-Targeted HIV Testing Campaigns

Abstract: The U.S. Centers for Disease Control and Prevention and the U.S. Preventive Services Task Force issued HIV testing recommendations, encouraging physicians to routinely test all adult patients for HIV. Studies have found that not all physicians are abiding by these guidelines, but that physician recommendations for HIV testing could encourage patients to get tested. Our study sought to determine physician preferences for a physician-targeted campaign to encourage them to offer HIV tests to their patients. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, 30% reported at least one interpersonal barrier (e.g., uncertainty about how to engage patients), and 41% reported at least one intrapersonal barrier (e.g., thinking that patients would be uncomfortable with, offended by, and/or refuse an HIV test), that prevented them from offering an HIV test (Arya, Patel, et al, 2016). Research has also shown that physicians, including our own in Houston, wanted data showing their patients were at risk for HIV (Arya, Phillips, Street, & Giordano, 2016). These findings, in the context of health behavior change models, led us to develop a physician-focused HIV testing video to tackle late and under-HIV testing in Houston.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Furthermore, 30% reported at least one interpersonal barrier (e.g., uncertainty about how to engage patients), and 41% reported at least one intrapersonal barrier (e.g., thinking that patients would be uncomfortable with, offended by, and/or refuse an HIV test), that prevented them from offering an HIV test (Arya, Patel, et al, 2016). Research has also shown that physicians, including our own in Houston, wanted data showing their patients were at risk for HIV (Arya, Phillips, Street, & Giordano, 2016). These findings, in the context of health behavior change models, led us to develop a physician-focused HIV testing video to tackle late and under-HIV testing in Houston.…”
Section: Background and Introductionmentioning
confidence: 99%
“…Although the goal of screening more than 80% of US adults for HIV is aspirational, research demonstrates that increased screening in health care settings would be cost effective, even for lower-risk groups, 6 and is key to ending the HIV epidemic. 4 Barriers to HIV testing in primary care settings include health care providers' unfamiliarity with national recommendations, 7,8 continued preference for risk-based screening, 8 assumptions about risk, 9 and HIV stigma. 9 However, studies have shown that improved HIV-testing uptake is possible using interventions such as patient text message reminders 10 and provider electronic medical record prompts.…”
Section: Discussionmentioning
confidence: 99%
“…While sending text messages to patients may be an innovative tool for promoting HIV prevention, patient-focused interventions may be bolstered by campaigns aimed at providers (Arya, Phillips, Street, & Giordano, 2016). Delivering tailored interventions to providers to improve their communications with racially and socioeconomically diverse populations can increase these providers’ confidence in managing patient interactions (Sullivan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%